A review development of rhombic drive mechanism used in the Stirling engines. (October 2017) - Erol, Derviş; Yaman, Hayri; Doğan, Battal
Abstract: Stirling engines, unlike internal combustion engines, are engines that generate power by using any type of heat energy source. In these engines, air, helium, and hydrogen are generally preferred as the working fluid. In terms of environment, Stirling engines have lower NOx, HC, and CO emission. The drive mechanisms vary according to the type of the engine. Suitable drive mechanisms need to be designed to obtain high power output from the engine. This study chronologically examines the efforts of development in Stirling engines. Stirling, Ericsson, and Carnot theoretical cycles are compared and their theoretical efficiency is show to be equal. It is shown that the thermodynamic properties of working fluids used in Stirling engines change according to the temperature. The effect of the working fluids on the engine's performance is discussed. The drive mechanisms used in Stirling engine throughout the historical development is studied in details. Theoretical and experimental studies performed on rhombic drive mechanisms that are distinguished among the drive mechanisms used in such engines by their advantages are examined. The rhombic drive mechanism is firstly used in Stirling engines by the Philips Company in 1953. After this date, the applications of the rhombic drive mechanism in various engines with different characteristics were assessed in terms of performance by companies and researchers. The comparison with other drive mechanisms shows that rhombic drive mechanism is the most suited drive mechanism for beta-type Stirling engines.